Profiling of Circulating Serum MicroRNAs in Children with Autism Spectrum Disorder using Stem-loop qRT-PCR Assay - Kichukova, Tatyana M; Popov, Nikolay T; Ivanov, Ivan S; Vachev, Tihomir I (Folia Medica, 2017)
Development of biomarkers for autism spectrum disorder (ASD) has still remained a challenge to date. Recently, alterations of the expression of microRNAs (miRNAs) in peripheral blood, serum and post-mortem brain tissue have been linked to ASD. miRNAs are known to be secreted by various cell types and can mediate transmission of information into recipient cells and to modulate their physiological functions. On this basis it is assumed that circulating miRNAs could be useful biomarkers for the diagnosis or prognosis of pathological conditions. The aim of this study was to test whether circulating miRNAs display differential expression profile in serum of ASD patients. The relative expression levels of 42 miRNAs were analyzed by stem-loop qRT-PCR assay in the serum of ASD patients compared to healthy controls. The results indicated that 11 miRNAs in ASD patients were substantially higher expressed than these in control subjects, and 29 miRNAs were lower expressed, respectively. In addition, target gene analysis displayed that the altered serum miRNAs targeted some important genes like alpha 1C subunit of voltage-dependent calcium channel, L type, (CACNA1C), beta 1 subunit of voltage-dependent calcium channel (CACNB1) and other genes involved in epigenetic processes like dicer 1, coding ribonuclease type III (DICER). Our results suggested that differentially expressed miRNAs in serum might be involved in ASD molecular pathways, and serum miR-424-5p, miR-197- 5p, miR-328-3p, miR-500a-5p, miR-619-5p, miR-3135a, miR-664a-3p, and miR- 365a-3p might be able to serve as potential biomarkers for ASD because they displayed significant alterations in the expression profile in children diagnosed with ASD.